Ailesel Marfan Sendromuna Bağlı İnme - M.taylan PEKÖZ; Filiz KOÇ (Cukurova Medical Journal, 2013)
Marfan syndrome is an autosomal-dominant disorder of connective tissue with musculoskeletal, ocular, lung, the skin and cardiovascular manifestations. We present a case of ischemic stroke who is diagnosed with Marfan Syndrome.